2012
DOI: 10.1007/s00229-012-0592-8
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoconvex domains spread over complex homogeneous manifolds

Abstract: Using the concept of inner integral curves defined by Hirschowitz we generalize a recent result by Kim, Levenberg and Yamaguchi concerning the obstruction of a pseudoconvex domain spread over a complex homogeneous manifold to be Stein. This is then applied to study the holomorphic reduction of pseudoconvex complex homogeneous manifolds X=G/H. Under the assumption that G is solvable or reductive we prove that X is the total space of a G-equivariant holomorphic fiber bundle over a Stein manifold such that all ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Hirschowitz showed that a pseudoconvex, infinitesimally homogeneous X that does not contain any inner integral curve is Stein [12,Proposition 3.4]. This is the starting point of our investigations of pseudoconvex homogeneous manifolds that are not Stein given in [10]. By the maximum principle any plurisubharmonic function on a complex manifold X is constant along every inner integral curve in X.…”
Section: Technical Preparationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hirschowitz showed that a pseudoconvex, infinitesimally homogeneous X that does not contain any inner integral curve is Stein [12,Proposition 3.4]. This is the starting point of our investigations of pseudoconvex homogeneous manifolds that are not Stein given in [10]. By the maximum principle any plurisubharmonic function on a complex manifold X is constant along every inner integral curve in X.…”
Section: Technical Preparationsmentioning
confidence: 99%
“…One has to determine the "directions of degeneracy" of plurisubharmonic functions in terms of a certain subset of g whose corresponding holomorphic vector fields "kill them". So in [10] we define the Hirschowitz annihilator A to be the connected Lie subgroup of G whose Lie algebra is given by…”
Section: Technical Preparationsmentioning
confidence: 99%
See 2 more Smart Citations
“…[7]). More recently, in [8], Gilligan, Miebach, and Oeljeklaus study the case of a pseudoconvex domain of any dimension, spread over a complex homogeneous manifold.…”
Section: Introductionmentioning
confidence: 99%